Yersinia pseudotuberculosis Anti-Inflammatory Components Reduce Trinitrobenzene Sulfonic Acid-Induced Colitis in the Mouse - Marceau, Michael (American Society for Microbiology, 2004)
Rectal instillation of trinitrobenzene sulfonic acid (TNBS) induces acute colitis in the mouse. We tested the efficacy of Yersinia pseudotuberculosis anti-inflammatory components in preventing TNBS-triggered colitis. Animals were orally inoculated with virulence-attenuated Yersinia cells (a phoP mutant) prior to TNBS administration. Under these experimental conditions, colonic lesions and tumor necrosis factor alpha mRNA levels were significantly reduced.